The study of dependency factors on foreign worker in construction industry : contractor perspective - Nur Hidayah, Aliman (2017)
Demands on labour force nowadays increased rapidly each year as the globalisation become a national core business, especially in construction sector. Construction sector provides all kind of national needs and Malaysia become a well-developed country in the world. Labour shortage in Malaysian construction industry is due to certain causes such as poor participation by local labour. In Malaysia, local youth would rather be unemployed despite working in the construction industry. There is an issue where the citizens have their own demand on choosing work which they refused to work as a construction labour. Furthermore, work in the construction sector is often stigmatized with 4D (dirty, dangerous, difficult, and demeaning). The industry has been forced to rely on foreign labour, mostly from neighbouring countries. Therefore, Malaysian construction sector has been a pulling factor for foreign labour migration in this country. Though foreign workers served to overcome the labour shortage in the Malaysian construction market, over-dependence on foreign workers have become a serious social problem. This study is conducted to examine the factors that influence the employers to hire foreign workers rather than local workers in the construction industry from the contractor viewpoint. The objectives of the study are: (a) to study the current scenarios related to the employment of foreign workers in the construction industry; (b) to investigate and identify the factors that influences the employers to employ foreign workers rather than local workers; and (c) to identify the most important factor that influence the employers to employ foreign workers rather than local workers. To achieve the objectives, data were collected using questionnaire forms which contain selection of short and predetermined as well as likert scale answers. The questionnaires were delegated to professionals in construction projects who have direct contacts with foreign workers. Only respondents from contractor companies registered under the CIDB grade G7 were chosen for this survey. There were 32 sets of questionnaires completed and analysed through the structured interviews and calculated using Relative Importance Index (RII) method. The data analysis showed that the factors attracting employers to employ foreign workers are based on economy, skill, social, attitude, and working environment factors. Overall comparison reflected that the most significant factor for employing foreign workers as compared to local workers is due to social factor. As a conclusion, the over dependency on foreign workers should be controlled and reduced so as to avoid any negative impacts that might affect the construction industry as well as the country itself.